Age-Related Hearing Loss in Mn-SOD Heterozygous Knockout Mice. (26th June 2013) - Kinoshita, Makoto; Sakamoto, Takashi; Kashio, Akinori; Shimizu, Takahiko; Yamasoba, Tatsuya
Abstract : Age-related hearing loss (AHL) reduces the quality of life for many elderly individuals. Manganese superoxide dismutase (Mn-SOD), one of the antioxidant enzymes acting within the mitochondria, plays a crucial role in scavenging reactive oxygen species (ROS). To determine whether reduction in Mn-SOD accelerates AHL, we evaluated auditory function in Mn-SOD heterozygous knockout (HET) mice and their littermate wild-type (WT) C57BL/6 mice by means of auditory brainstem response (ABR). Mean ABR thresholds were significantly increased at 16 months when compared to those at 4 months in both WT and HET mice, but they did not significantly differ between them at either age. The extent of hair cell loss, spiral ganglion cell density, and thickness of the stria vascularis also did not differ between WT and HET mice at either age. At 16 months, immunoreactivity of 8-hydroxydeoxyguanosine was significantly greater in the SGC and SV in HET mice compared to WT mice, but that of 4-hydroxynonenal did not differ between them. These findings suggest that, although decrease of Mn-SOD by half may increase oxidative stress in the cochlea to some extent, it may not be sufficient to accelerate age-related cochlear damage under physiological aging process.